Structure and Phase State of Bone Apatite of Calcified Aortic Fragments with Osteoporosis - Ya.V. Khyzhnya; A.V. Ataman; A.S. Stanislavov; V.N. Kuznetsov; S.M. Danilchenko (Журнал нано- та електронної фізики)
The paper represents the results of the study on the structure and phase composition of bone apatite and fragments of calcified aorta of the same experimental animal with model osteoporosis. Examination by the X-ray and electron diffraction, electron microscopy and infrared spectroscopy reveals that pathological calcification of rabbit aorta with model osteoporosis in crystal-chemical terms is the imperfect calcium apatite Ca10(PO4)6(OH)2. Temperature growth of ectopic apatite crystals during annealing at 900C is similar to bioapatite of bone.